The Application of Membrane Separation Technology in the Pharmaceutical Industry - Ruirui Ma; Juan Li; Ping Zeng; Liang Duan; Jimin Dong; Yunxia Ma; Lingkong Yang (Membranes, 2024)
With the advancement in membrane technology, membrane separation technology has been found increasingly widespread applications in the pharmaceutical industry. It is utilized in drug separation and purification, wastewater treatment, and the recycling of wastewater resources. This study summarizes the application history of membrane technology in the pharmaceutical industry, presents practical engineering examples of its applications, analyzes the various types of membrane technologies employed in the pharmaceutical sector, and finally, highlights the application cases of renowned international and Chinese membrane technology companies in the pharmaceutical field.